Need Analysis of Designing Collaborative Learning-Based English for Digital Marketing Textbook - Sri Waluyo; Fatimah Nur Arifah; Taher Razan; Aspuri Rahmadani Khairun Nisa (UNIVERSITAS PGRI YOGYAKARTA, 2022)
Abstract This study aims to analyze the need in designing English for Digital Marketing textbook based on collaborative learning. The approach employed in this study was research and development. The analysis technique applied was descriptive qualitative. Participants in this study were two lecturers who teach English courses for non-English study programs and 30 non-English program students majoring in Informatics and Information Systems. Need analysis was obtained through a questionnaire distributed to all participants. In addition, this study also conducted interviews with some of the participants to obtain a more comprehensive picture. The findings showed that all participants agreed that English for Digital Marketing textbook to be developed as it would be helpful for them in the teaching and learning process. The participants also suggested that the textbook should be not only applicable and close to the real conditions but also attractive. Keywords: Need Analysis, English Textbook, Digital Marketing, Collaborative Learning